ANALISIS PELANGGARAN HAK ASASI MANUSIA DALAM KERUSUHAN PERTANDINGAN SEPAK BOLA DI KANJURUHAN : PERSPEKTIF HUKUM NASIONAL DAN INTERNASIONAL - Trio Fatra Nusantara; Farhana (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
The riot that occurred on October 1, 2022 at Kanjuruhan Stadium, Malang, killed 135 people and injured hundreds of others. This incident has been in the public spotlight because it shows serious violations of human rights, both from the perspective of national law and international law. This study aims to identify the forms of human rights violations that occurred in these incidents, analyze violations of international standards such as FIFA regulations and the International Covenant on Civil and Political Rights (ICCPR), and examine Islamic views on human rights protection. The research methods used are normative juridical approaches and empirical juridical approaches, with descriptive qualitative data analysis techniques. The results of the study showed that the Kanjuruhan riots involved violations of the right to life, the right to security, the right to health, the rights of children, and the right to justice. The use of tear gas inside the stadium by police officers not only violates FIFA regulations but also reflects an act of excessive use of force that threatens the safety of civilians. In addition, the match organizers were also considered negligent because they sold tickets beyond the stadium's capacity and did not provide adequate evacuation routes. In the perspective of Islamic law, actions that cause mass loss of life without justice are contrary to the principles of sharia maqashid and the obligation to protect human souls. This study recommends reforms in the security system of sports matches, increased accountability of security forces, and a thorough evaluation of human rights regulations at both the national and international levels. Fair and transparent law enforcement is urgently needed so that public trust in the state and law enforcement officials can be restored.